PARE0016 MINDFULNESS-BASED STRESS REDUCTION TO IMPROVE DEPRESSIVE SYMPTOMS AND RHEUMATOID ARTHRITIS-RELATED CLINICAL OUTCOMES: RESULTS FROM A FEASIBILITY AND ACCEPTABILITY TRIAL. (2nd June 2020) - Beaulieu, M. C.; Gaboury, I.; Carrier, N.; Dobkin, P.; Gervais, F.; Gendron, F.; Roberge, P.; Dagenais, P.; Roux, S.; Boire, G.
Abstract : Background: Despite available highly effective pharmacological treatments, up to 30% of current rheumatoid arthritis (RA) patients remain in quasi-remission, where inflammation is controlled but patients still report unacceptable levels of negative impact of RA (high Patient Global Assessment (PGA) on a 0-10 visual analog scale). PGA levels correlated with depressive symptoms assessed by Center for Epidemiologic Studies- Depression (CES-D) scores. Mindfulness-Based Stress Reduction (MBSR) is relatively inexpensive and reduces both anxiety and depression in several conditions. Objectives: To complete a feasibility and acceptability study paving the way for a randomized controlled trial (RCT) of MBSR to improve depressive symptoms and clinical outcomes in RA patients in quasi-remission. Methods: A standardized 8-week MBSR program in adults with controlled inflammatory disease (stable SJC ≤ 2/66 and normal CRP; stable treatments) but high CES-D scores (2 groups), high CES-D or anxiety scores (1 group), or PGA higher than Physician Evaluation of Disease Activity (EVA) by ≥2 (1 group). Feasibility was documented using process indicators. Outcomes were measured at baseline and 6 months after the end of MBSR. Disease activity scores (SDAI) and questionnaires on depressive symptoms (CES-D), HAQ, sleep (VAS), fatigue and pain (SF-36), anxiety (GAD-7), PGA were collected. Qualitative interviews based on a theoretical framework of acceptability were conducted following the post-MBSR evaluation. Results: We report on the first 21 patients (mean age 59, 91% females) having completed their 6-month follow up evaluation. Factors leading to higher recruitment rates were 1) using pragmatic scores to identify eligible patients (e.g. EVA and PGA), 2) no formal clinical evaluation of mental health and no emphasis on depression in the recruitment material. MBSR had a highly significant positive impact on depressive symptoms (p=0.003) and anxiety (p=0.025) (Figure), and positive impact on quality of sleep and HAQ. No change in SDAI or joint counts was noted. During a qualitative interview of 13 participants, most reported that MBSR helped them control their reactions to daily stressful situations. Perceptions were almost uniformly positive towards MBSR, and most appeared to have integrated some part of it in their daily life. No side effects were reported. Conclusion: Although recruitment was challenging, a MBSR trial in RA patients in quasi-remission was found acceptable and feasible. Positive impacts on mood and on clinical outcomes were observed. Anxiety and depression scores appear the most sensitive to change and are recommended as the primary outcome for an eventual RCT. MBSR added to conventional treatments might help empower RA patients towards self-management. Acknowledgments: Grant support from Canadian Initiative for Outcomes in Rheumatology cAre (CIORA) Disclosure of Interests: Marie-Claude Beaulieu: None declared, Isabelle Gaboury: None declared, Nathalie Carrier: None declared, Patricia Dobkin: None declared, France Gervais: None declared, Françoise Gendron: None declared, Pasquale Roberge: None declared, Pierre Dagenais: None declared, Sophie Roux: None declared, Gilles Boire Grant/research support from: Merck Canada (Registry of biologices, Improvement of comorbidity surveillance) Amgen Canada (CATCH, clinical nurse) Abbvie (CATCH, clinical nurse) Pfizer (CATCH, Registry of biologics, Clinical nurse) Hoffman-LaRoche (CATCH) UCB Canada (CATCH, Clinical nurse) BMS (CATCH, Clinical nurse, Observational Study Protocol IM101664. SEROPOSITIVITY IN A LARGE CANADIAN OBSERVATIONAL COHORT) Janssen (CATCH) Celgene (Clinical nurse) Eli Lilly (Registry of biologics, Clinical nurse), Consultant of: Eli Lilly, Janssen, Novartis, Pfizer, Speakers bureau: Merck, BMS, Pfizer